Model pembelajaran berbasis masalah pada peningkatan kemampuan pemahaman konsep matematis peserta didik kelas VIII pada materi sistem persamaan linear dua variabel - Lestari, Fauziah; Minarti, Eva Dwi; Riajanto, Marchasan Lexbin Elvi Judah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This study aims to evaluate the extent to which students understanding of mathemmatical concepts improves when thaught using the problem based learning model compared to those taught using the conventional model, discovery learning. The research employs an experimental method with a quasi eksperimental design, dividing students into two groups: an experimental class and a control class. The study’s populasi includes all eight grade students at SMP Terpadu Al Mumin. Data Collection was carried out using to measure student’s understanding of mathematical concepts. The collected data were then processed using IBM SPSS 26, with data analysis encompassing normality tests, homogenity tests, and independent two sample t-test. The results indicate that students taught using the problem based learning model show more effective mathematical conceptual understanding compared to those taught using the conventional learning model. Additionally, there was a significant improvement in the understanding of mathematical concepts among students exposed to the problem based learning model compared to those using the conventional teaching method.